2021
DOI: 10.1021/acs.jafc.1c03070
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Micellar Nanoparticles by Enzymatic Hydrolysis of High-Density Lipoprotein for the Formation and Stability of High Internal Phase Emulsions

Abstract: In this study, the influence of pH on the conformational state of EHT, which was obtained from the enzymatic hydrolysis of trypsin, and the stabilizing properties of high internal phase emulsions have been demonstrated. Critical micelle concentration and transmission electron microscopy results exhibited the formation of micellar nanoparticles with mean diameters ranging from 108 to 1359.5 nm. The results of solubility, surface hydrophobicity, and conformations indicated that EHT tended to act as particulate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Additionally, Liu et al found that EYPNs with various sizes and highly pH-dependent structures could act as an efficient particulate emulsifier to stabilize O/W high-internal-phase emulsions (Figure e). The compact adsorption of EYPNs could explain the outstanding stability at the interface and the formation of a three-dimensional network …”
Section: Application Of Fpdmps In Food Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, Liu et al found that EYPNs with various sizes and highly pH-dependent structures could act as an efficient particulate emulsifier to stabilize O/W high-internal-phase emulsions (Figure e). The compact adsorption of EYPNs could explain the outstanding stability at the interface and the formation of a three-dimensional network …”
Section: Application Of Fpdmps In Food Processesmentioning
confidence: 99%
“…The self-assembly of FPDMPs into micellar structures has been extensively reported. For example, The amphiphilic egg yolk peptides obtained from enzymatic hydrolysis of purified defatted egg yolk proteins can self-assemble into micellar nanostructures under aqueous conditions at the CMC of about 0.1 mg/mL. , The observed results were attributed to the increased abundance of hydrophilic amino acids, including glutamic acid (Glu), lysine (Lys), arginine (Arg), aspartic acid (Asp), and serine (Ser), in the amphiphilic egg yolk peptides. Additionally, it has been found that BLP partially hydrolyzed α-la released amphiphilic peptides could self-assemble into micelle structures at a low CMC (0.75 mg/L). , Partial hydrolysis exposes the hydrophobic moieties of α-la, leading to the self-assembly of these peptides into micelles through hydrophobic interactions .…”
Section: Self-assembled Fpdmps With Diverse Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymatic hydrolysis significantly improved the solubility and emulsifying properties of hydrolysates. The authors also used the enzymatic hydrolysis of trypsin to obtain the EHT (Liu et al, 2021 ). The amphiphilic peptides exhibited self-assembly behaviors into micellar nanoparticles with various sizes, depending on the pH values.…”
Section: Introductionmentioning
confidence: 99%